Characteristics of serum neurofilament light chain as a biomarker in hereditary spastic paraplegia type 4. Issue 3 (16th February 2022) - Kessler, Christoph; Serna‐Higuita, Lina Maria; Wilke, Carlo; Rattay, Tim W.; Hengel, Holger; Reichbauer, Jennifer; Stransky, Elke; Leyva‐Gutiérrez, Alejandra; Mengel, David; Synofzik, Matthis; Schöls, Ludger; Martus, Peter; et al.
Abstract: Objective: While the anticipated rise of disease‐modifying therapies calls for reliable trial outcome parameters, fluid biomarkers are lacking in spastic paraplegia type 4 (SPG4), the most prevalent form of hereditary spastic paraplegia. We therefore investigated serum neurofilament light chain (sNfL) as a potential therapy response, diagnostic, monitoring, and prognostic biomarker in SPG4. Methods: We assessed sNfL levels in 93 patients with SPG4 and 60 healthy controls. The longitudinal study of sNfL levels in SPG4 patients covered a baseline, 1‐year follow‐up and 2‐year follow‐up visit. Results: Levels of sNfL were significantly increased in patients with genetically confirmed SPG4 compared to healthy controls matched in age and sex ( p  = 0.013, r  = 0.2). Our cross‐sectional analysis revealed a greater difference in sNfL levels between patients and controls in younger ages with decreasing fold change of patient sNfL elevation at older ages. Over our observational period of 2 years, sNfL levels remained stable in SPG4 patients. Disease severity and progression did not correlate with sNfL levels. Interpretation: Our longitudinal data indicate a stable turnover of sNfL in manifest SPG4; therefore, sNfL levels are not suitable to monitor disease progression in SPG4. However, sNfL may be valuable as a therapy response biomarker, since its turnover could be modified by interventions. As the course of sNfL levels appears to be most dynamic around the onset of SPG4, the ability to detect a therapy response appears to be especially promising in younger patients, matching the need to initiate treatment in early disease stages.